Assessment of odor hedonic perception: the Sniffin’ sticks parosmia test (SSParoT) - Liu, David T.; Welge-Lüssen, Antje; Besser, Gerold; Mueller, Christian A.; Renner, Bertold (Scientific reports, 2020)
Qualitative olfactory dysfunction is characterized as distorted odor perception and can have a profound effect on quality of life of affected individuals. Parosmia and phantosmia represent the two main subgroups of qualitative impairment and are currently diagnosed based on patient history only. We have developed a test method which measures qualitative olfactory function based on the odors of the Sniffin’ Sticks Identification subtest. The newly developed test is called Sniffin’ Sticks Parosmia Test (SSParoT). SSParoT uses hedonic estimates of two oppositely valenced odors (pleasant and unpleasant) to assess hedonic range (HR) and hedonic direction (HD), which represent qualitative olfactory perception. HR is defined as the perceivable hedonic distance between two oppositely valenced odors, while HD serves as an indicator for overall hedonic perception of odors. This multicenter study enrolled a total of 162 normosmic subjects in four consecutive experiments. Cluster analysis was used to group odors from the 16-item Sniffin’ Sticks Identification test and 24-additional odors into clusters with distinct hedonic properties. Eleven odor pairs were found to be suitable for estimation of HR and HD. Analysis showed agreement between test–retest sessions for all odor pairs. SSparoT might emerge as a valuable tool to assess qualitative olfactory function in health and disease.